Karakteristik vegetatif dan taksasi produksi kopi robusta tahun 2018 dan 2019 (Survey pada perkebunan kopi rakyat di Dusun Mandang, Desa Sucen, Kecamatan Gemawang, Kabupaten Temanggung) - Yohana Theresia Maria Astuti; Tri Nugraha Budi Santosa; Dian Pratama Putra; Enny Rahayu; Agus Solifudin; Galeh Haykal Nugraha (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
This study aims to evaluate the dinamics of coffee production in Mandang, Sucen Village, Gemawang District, Temanggung on 2018 and 2019. The research was carried out at people coffee plantation in Mandang Hamlet, Sucen Village, Temanggung. Research using survey methods. Observation of performance with 30 samples taken by purposive sampling technique on 3 clones. Land suitability analysis was carried out at 3 observation points. The results obtained are: The vegetative characteristics of robusta coffee BP 288 and BP 409 are better than BP 358 clones, while the robusta coffee production is the same on various clones and plantation location. The long dry season in 2018 and 2019 has an effect on the decline of the number of leaves and coffee production in 2019 compared to 2018 in Mandang Hamlet, Sucen Village, Gemawang district, Temanggung.